Toward the Paris Agreement Implementation Impact on Electricity Sector: The Emerging Reality - EstevÃ£o, JoÃ£o (International Journal of Energy Economics and Policy, 2020)
The signing of the Paris Agreement has created a new avenue of research because it sets out a global challenge to tackle climate change by limiting global warming. The topic is of growing interest involving investigators from different scientific areas, with the focus being on the increase in the consumption of renewable energies and, consequently, on the reduction of carbon dioxide emissions. From the research, most studies use simulation models to verify whether the goals set out in the Agreement are achievable. This paper presents an analytical review of the publications in order to assess the attention and awareness focused on the Paris Agreement and, specifically, the electricity sector. For this purpose, our study uses a bibliometric analysis considering authors, the types of documents, the title of the sources, the year of publication, the institutions, the languages, the countries of origin, and related concepts. In conclusion, the study's most frequent terms are “Paris Agreement”, “carbon”, “climate change” and “renewable energy”. It also concludes that the topic is of growing interest within academia. The results of this paper provide to energy researchers a relevant overview of the tendencies and scope of the Paris Agreement. Keywords: Paris Agreement; Electricity; Bibliometric analysis JEL Classifications: K32, O13, Q43, Q48, Q56 DOI: https://doi.org/10.32479/ijeep.10276